BIMBINGAN DAN KONSELING ISLAM DENGAN MEDIA BRAILLE DALAM MENINGKATKAN MOTIVASI DIRI PADA PENYANDANG TUNA NETRA (Jurusan Bimbingan dan Konseling Islam, 2013)
In this regard, the field study used descriptive qualitative method of comparative analysis is to compare the implementation of the ICC on the ground with the theories of development in accordance with the issue. The data used to determine the final result of the implementation of the ICC is achieved by comparing the state of the client before and after the implementation of the ICC. In this study concluded that the implementation of the ICC with Braille media to motivate yourself in with the Blind is to engage with clients, current behavior, self-assess, plan for responsible action, does not accept the reasons, and there is no penalty. And the implementation was successful, it can be evidenced by the change in the apparent increased motivation on the client after getting BKI heading in a positive direction and better than increasing the client's self motivation before and after getting BKI with Braille media.Keywords : Islamic Guidance and Counselling, Self Motivation, Media Braille and the Blind .